The making of the Philippine president a textual analysis of mythical archetypes in the TV news reports of the 2010 presidential elections - Sarmenta, Severino R. Jr (Plaridel, 2015)
Access online through this link: https://www.plarideljournal.org/article/the-making-of-the-philippine-president-a-textual-analysis-of-mythical-archetypes-in-the-tv-news-reports-of-the-2010-presidential-elections